Organizational Cronyism as an Antecedent of Ingratiation: Mediating Role of Relational Psychological Contract - Shaheen, Sadia; Bari, Muhammad Waseem; Hameed, Filza; Anwar, Muhammad Mudassar (Frontiers in Psychology, 2019)
The present study investigates the relatively less explored construct organizational cronyism as an antecedent of employees’ ingratiation. Moreover, the role of the relational psychological contract as a mediator between organizational cronyism and ingratiation is also examined. The data were collected from employees working in different ministerial offices, such as the ministry of defense production, human rights, parliamentary affairs, petroleum, and natural resources, in Islamabad, Pakistan. Through a convenience sampling approach, 250 employees provided data for this study. Due to sensitivity and less approachability to these organizations, the convenience sampling technique was used. The data were collected in two waves with 12-week intervals. The results confirm that organizational cronyism is significantly related to the relational psychological contract, which in turn results in employees’ ingratiation. The employees who have close ties with their leaders and enjoy extraordinary favors from their leaders, display more compliance behavior as compared to those employees who have distance from their leaders.